Estrés y su relación con la satisfacción laboral de las enfermeras del hospital “Sagrado Corazón de Jesús” del cantón Quevedo, primer semestre 2018. - Cedeño Andrade, Guisella Fernanda (2018)
The purpose of the investigation was: To determine the influence of stress and its relation with the job satisfaction of the nurses of the “Sacred Heart of Jesus” hospital. A descriptive, field study was carried out since it was posible to carry out surveys and observations. The selected participants were 75 nurses. The instruments used to assess work stress were: a survey applied to the nursing staff in which situations that were stressful in their current service were evidenced. Another is the questionnaire that helped to evaluate the different aspects that produce job satisfaction or dissastisfaction. Subsequently, it was obtained as a result that 67% of the nursing staff are being affected by stress, but at the same time they feel moderate work satisfaction, so it allows to establish the proposal to be applied through training on training methods and practices aimed at nursing staff, which will help reduce the level of stress.